Endobronchial ultrasound: A novel screening test for pulmonary hypertension prior to major pulmonary surgeryCentral MessagePerspective - Nathaniel Deboever, MD, MSc; George A. Eapen, MD; Roberto F. Casal, MD; Jean-Bernard Durand, MD; Michael A. Eisenberg, MD; Hope Feldman, MD, MSc; Celestino May, MD, MAEd; Zohra Ali, APRN, MSc; David C. Rice, MB, BCh; Reza J. Mehran, MDCM, MSc (JTCVS Techniques)
Objectives: Pulmonary hypertension (PH) is an important physiologic variable in the assessment of patients undergoing major thoracic operations but all too often neglected because of the need for right heart catheterization (RHC) due to the inaccuracy of transthoracic echocardiography. Patients with lung cancer often require endobronchial ultrasound (EBUS) as part of the staging of the cancer. We sought to investigate whether EBUS can be used to screen these patients for PH. Methods: Patients undergoing a major thoracic operation requiring EBUS for staging were included prospectively in the study. All patients had also a RHC (gold standard). We aimed to compare the pulmonary artery pressure measurements by EBUS with the RHC values. Results: A total of 20 patients were enrolled in the study. The prevalence of abnormal pulmonary artery pressure was 65% based on RHC. All patients underwent measurement of the pulmonary vascular acceleration time (PVAT) by EBUS with no adverse events. Linear regression analysis comparing PVAT and RHC showed a correlation (r = −0.059, −0.010 to −0.018, P = .007). A receiver operator characteristic curve (area under the curve = 0.736) was used to find the optimal PVAT threshold (140 milliseconds) to predict PH; this was used to calculate a positive and negative likelihood ratio following a positive diagnosis of 2.154 and 0.538, respectively. Conclusions: EBUS interrogation of pulmonary artery hemodynamic is safe and feasible. EBUS may be used as a screening test for PH in high-risk individuals.